Pengaruh Fitur Tiktok Shop pada Keputusan Pembelian Konsumen di Soloraya: Entertainment sebagai Mediator - Herlian Bhara Yanottama; Ihwan Susila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the influence of TikTok Shop features on consumer purchasing decisions, with entertainment as a mediating factor. Using the Partial Least Squares (PLS) methodology via SmartPLS3, data from 118 respondents in Soloraya were collected online and analyzed to understand the direct and indirect effects of perceived usefulness, interactivity, and relevance on purchasing decisions. The results indicate that entertainment significantly enhances purchasing decisions, both directly and as a mediator between relevance, interactivity, and usefulness. Additionally, perceived usefulness and relevance positively contribute to purchasing decisions, with entertainment strengthening their effects. This research contributes to the digital marketing literature by emphasizing the importance of entertainment in shaping consumer behavior on social commerce platforms like TikTok Shop. The findings provide practical insights for businesses looking to optimize online consumer engagement and purchasing outcomes.